Actualidad política y constitucional francesa (2006-2007) - Sánchez Navarro, Angel (Teoría y Realidad Constitucional, 2007)
The last twelve months have been undoubtedly marked by the French electoral calendar. Despite of that, institutional life has continued, producing three new constitutional reforms (with particular reference to the constitutional prohibition of the death penalty), and some other legal changes which, sometimes submitted to the Constitutional Court, deserve some closer consideration.